Peningkatan Hasil Belajar Bahasa Indonesia pada Materi Identifikasi Teks Kebudayaan Kalimantan Tengah melalui Pendekatan Cullturally Responsive Teaching Berbantuan Media Wordwall pada Peserta Didik Kelas IV SDN-7 Panarung - Pratama, Juniardi; Azahari, Abd Rahman; Sugiyanto, Roso; Afrom, Ichyatul (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This research is class action research (PTK). The results of this study indicate that through the Cullturally Reponsive Teaching approach assisted by Wordwall media has a positive contribution in improving Indonesian language learning outcomes. This can be seen in (1) The activity of students in learning Indonesian by applying the Cullturally Reponsive Teaching approach with the help of Wordwall media is good. (2) There is an increase in Indonesian language learning outcomes in fourth grade students of SDN 7 Panarung Palangkaraya by using Cullturally Reponsive Teaching assisted by Wordwall media. This can be seen from the results of the pre-action (Pre-test) average value of 56 with a percentage of classical completeness of 26%. Furthermore, in cycle I the average value obtained was 66 with a percentage of 76% classical completeness and in cycle II the average value obtained was 100 with 100% classical completeness.